Microporous Cyclic Titanium‐Oxo Clusters with Labile Surface Ligands. (28th November 2017) - Zhao, Chaowei; Han, Ying‐Zi; Dai, Shuqi; Chen, Xumao; Yan, Juanzhu; Zhang, Weijie; Su, Haifeng; Lin, Shuichao; Tang, Zichao; Teo, Boon K.; Zheng, Nanfeng
Abstract: By using ethylene glycol and monocarboxylic acid as surface ligands, a series of cyclic Ti‐oxo clusters (CTOC) with permanent microporosity are successfully synthesized. With a cyclic Ti32 O16 backbone made of eight connected Ti4 tetrahedral cages that are arranged in a zigzag fashion, the clusters have a "donut" shape with an inner diameter of 8.3 Å, outer diameter of 26.9 Å and height of 10.4 Å. While both inner and outer walls of the "donut" clusters are modified by double‐deprotonated ethylene glycolates, their upper and lower surfaces are bound by carboxylates and mono‐deprotonated ethylene glycolates. The clusters are readily packed into one‐dimensional tubes which are further arranged in two different modes into crystalline microporous solids with surface areas over 660 m 2 g −1, depending on the surface carboxylates. The solid with olefin‐bearing carboxylates exhibits a superior CO2 adsorption capacity of 40 cm 3 g −1 at 273 K under 1 atm. Moreover, the mono‐deprotonated ethylene glycolates on the clusters are demonstrated to be highly exchangeable by other alcohols, providing a nice platform for creating microporous solids or films with a wide variety of surface functionalities.